2008
DOI: 10.1369/jhc.2008.952192
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Runx2, Osterix, and Osteopontin in Tooth Root Formation in Rat Molars

Abstract: (HN) S U M M A R Y Cementogenesis starts with the differentiation of cementoblasts. Mature cementoblasts secrete cementum matrix. Cementum components are similar to bone; moreover, cementoblasts possess many characteristics similar to those of osteoblasts. Runx2 and osterix, the transcriptional factors for osteoblast differentiation, participate in tooth formation. However, the characteristics of Runx2 and osterix during the differentiation process of cementoblasts remain unclear. In this study, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 26 publications
(28 reference statements)
2
74
0
3
Order By: Relevance
“…The runt family transcription factor Runx2 is an essential transcription factor for osteoblastic differentiation [28]. A downstream gene of Runx2 [29], Osx, is a zinc finger-containing transcription factor required for osteoblastic differentiation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The runt family transcription factor Runx2 is an essential transcription factor for osteoblastic differentiation [28]. A downstream gene of Runx2 [29], Osx, is a zinc finger-containing transcription factor required for osteoblastic differentiation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…OPN reactivity in the cement line and surface of cementum and alveolar bone might be induced by osterix expression. Their strong localization in periodontal tissues when 100 g of heavy force was applied indicates that they might be molecules linking mechanostressing and osteogenic and odontogenic differentiation 20,23,24 and might be involved in bone, PDL, and cementum remodeling during orthodontic tooth movement. The precise relationship between OPN and osterix during periodontal tissue remodeling in response to heavy force could not be ascertained with the current methodology.…”
Section: Discussionmentioning
confidence: 99%
“…16 Osterix triggers the formation and secretion of matrix such as cementum, dentin, and bone, indicating that osterix might be a useful marker of differentiation of cementoblasts, osteoblasts, and odontoblasts. 20 Previous studies showed that the heavy forces produced less tooth movement and more root resorption compared with light forces. Orthodontic tooth movement with heavy forces led to the increased expression of proteins related to cementum and alveolar bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that Runx2 and its downstream target OSX play critical roles in cementogenic differentiation, which is important for osteogenesis. 30,31 Furthermore, OSX particularly controls the formation of cellular cementum. 32 During in vitro cementogenic differentiation, rhPAI-1 increased Runx2 expression at 7 days and subsequently increased OSX expression at 14 days.…”
Section: Recombinant Human Pai-1-induced Osx and Cemp1 Expression Is mentioning
confidence: 99%